A spatial model for studying the effects of climatic change on the structure of landscapes subject to large disturbances - Baker, William L.; Egbert, Stephen L.; Frazier, George F. (Ecological modelling, 1991)
Global warming may have many consequences for natural ecosystems, including a change in disturbance regimes. No current model of landscapes subject to disturbance incorporates the effect of climatic change on disturbances on decade to century time scales, or addresses quantitative changes in landscape structure as disturbances occur. A new computer simulation model, DISPATCH, which makes use of a geographical information system for managing spatial data, has been developed for these purposes. The concept and structure of the DISPATCH model are described here, and a hypothetical example of its use is illustrated, but the model requires refinement before it can be used to predict the effects of global warming on specific landscapes. The model includes provisions for (1) temporally varying weather conditions and their effect on disturbance sizes, and (2) the effect of spatial variation in vegetation condition and physical setting on the probability of disturbance initiation and spread. The potential use of the model is illustrated with a hypothetical example in which the age structure of disturbance patches is monitored for a 250-year period as weather fluctuates. The model run suggests that landscape structure fluctuates even if a disturbance regime remains constant.